Kikuchi-Fujimoto disease with multisystem involvement: A case report - Sahu, Vinay Kumar (Indian Journal of Child Health, 2016)
Kikuchi-Fujimoto disease (KFD) is a self-limited, usually benign condition of unknown etiology characterized by fever and cervical lymphadenitis. Multisystem involvement is not very common. We report a case of a 14-year-old Chinese boy who presented with prolonged fever, rashes, cervical lymphadenitis, oral ulcers, and weight loss eventually diagnosed with Kikuchi’s disease. This case is interesting as the child subsequently developed multisystem involvement secondary to Kikuchi disease. The child recovered and remains well on follow-up clinic visits. KFD may have to be differentiated from many other infective, inflammatory, and malignant disorders. Diagnosis is confirmed by characteristic histopathological findings on excision lymph node biopsy. Long-term careful monitoring of these patients for signs and symptoms of evolving systemic lupus erythematosus or other autoimmune disorders is required.